A case of unexpected travelers - Castelbranco-Silva, Ana; Ferreira Lança, Ana; Robalo Nunes, Tomás; Martins, Rita; Gomes Ferreira, Maria (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Human myiasis is the infestation of humans with dipterous larvae. Cutaneous myiasis is the most common form and is one of the most common travel-associated skin diseases. The condition should be suspected when furuncle or boil-like skin lesions are observed in patients travelling from endemic regions. Herein is described the case of a toddler who had travelled from Guinea-Bissau seven days earlier and presented with a six-day history of painful furuncle-like swellings on the left thigh and scrotum. Two larvae were collected from one of the lesions, and entomological analysis confirmed the diagnosis of cutaneous myiasis. Complete larvae extraction is the primary treatment goal, and adequate preservation of the maggots is essential for public health analysis.